Wireless inertial sensor system for hammer throwing - Tiedemann Stefan; Spelly Gwen; Witte Kerstin (International Journal of Computer Science in Sport)
The aim of this study is to integrate an inertial sensor inside a hammer to allow a realtime feedback. In the first step we build our own prototype to measure the radial acceleration. In the second step there is a validation with an infrared camera system. It is a comparison between the radial acceleration along the wire axis, that is measured by the sensor against the velocity that is delivered by the infrared camera system. As a result, significant correlation was observed between the measured velocity and the acceleration (r = 0.99, p < 0.001). These suggest that this system can used in the training to improve the technique of the hammer throw.